A Comparative Genomic Analysis of Energy Metabolism in Sulfate Reducing Bacteria and Archaea - Pereira, Inês A. C.; Ramos, Ana R.; Grein, Fabian; Marques, Marta C.; Da Silva, Sofia M.; Venceslau, Sofia S. (Frontiers in Microbiology, 2011)
The number of sequenced genomes of sulfate-reducing organisms (SRO) has increased significantly in the recent years, providing an opportunity for a broader perspective into the energy metabolism of such organisms. In this work we carried out a comparative survey of energy metabolism genes found in twenty-five available genomes of SRO. This analysis revealed a higher diversity of possible energy conserving pathways than classically considered to be present in these organisms, and permitted the identification of new proteins not known to be present in this group. The Deltaproteobacteria (and Thermodesulfovibrio yellowstonii) are characterized by a large number of cytochromes c and cytochrome c-associated membrane redox complexes, indicating that periplasmic electron transfer pathways are important in these bacteria. The Archaea and Clostridia groups contain practically no cytochromes c or associated membrane complexes. However, despite the absence of a periplasmic space, a few extracytoplasmic membrane redox proteins were detected in the Gram-positive bacteria. Several ion-translocating complexes were detected in SRO including H+-pyrophosphatases, complex I homologues, Rnf and Ech/Coo hydrogenases. Furthermore, we found evidence that cytoplasmic electron bifurcating mechanisms, recently described for other anaerobes, are also likely to play an important role in energy metabolism of SRO. A number of cytoplasmic [NiFe] and [FeFe] hydrogenases, formate dehydrogenases and heterodisulfide reductase-related proteins are likely candidates to be involved in energy coupling through electron bifurcation, from diverse electron donors such as H2, formate, pyruvate, NAD(P)H, β-oxidation and others. In conclusion, this analysis indicates that energy metabolism of SRO is far more versatile than previously considered, and that both chemiosmotic and flavin-based electron bifurcating mechanisms provide alternative strategies for energy conservation.